Skills Transformation in Higher Education: Perceptions of Foreign Language Lecturers - M. Gamze Bozgöz; Bekir S. Gür (Üniversite Araştırmaları Dergisi)
Utilizing in-depth interviews with 14 lecturers teaching English in foreign language departments at two state and two private universities in Ankara, capital of Turkey, this study aims to discover the direction of skills transformation of these lecturers. The results show that they assumed new roles and acquired new skills, but also lacked some critical skills. Work intensification, inadequate professional development opportunities, exclusion from decision-making processes, and increasing managerial control result in deskilling in both research and pedagogy. The research findings also show that work environment is unable to provide professional development and to increase the motivation of the lecturers teaching English, placing them at a disadvantage in universities. Lecturers who think that their ideas are considered unimportant or ignored tend to lose their motivation to improve some professional skills. This study revealed that the most noticeable issue facing foreign language lecturers in the higher education system is their marginalized and undervalued status.